On the role of present bias and biased price beliefs in household energy consumption - Werthschulte, Madeline; Löschel, Andreas (Journal of environmental economics and management, 2021)
The intermittency of energy billing may give rise to different biases or misperceptions, such that household energy demand deviates from its true optimum. This study investigates such deviations by linking variation in present-biased preferences and energy price beliefs to variation in energy consumed. Using both a survey and incentivized experiments, we gather measures of present bias as well as price beliefs, and observe participants’ true electricity consumption. Our main finding is that participants with present bias are predicted to consume on average 9 to 10 percent more electricity than participants with time-consistent discounting. Our results further suggest that neither the true marginal electricity price nor the perceived marginal electricity price can predict electricity consumption. These findings raise doubt as to the effectiveness of classic price-based policies in reducing household energy consumption.
Gesehen am 28.11.2023